Exame Celpe-Bras: uma investigação sobre o papel do entrevistador na interação face a face - Bottura, Eleonora Bambozzi (Universidade Federal de São Carlos, 2014)
This work aims at investigating interviewer s role in Celpe-Bras second term 2012 edition. We consider that the role of the interviewer can affect positively or negatively the examinee s performance as well as the examinee s proficiency. Studies have focused on the impact of the interviewer s role in performance. Important researches investigate interviewer s attitudes can benefit or harm examinee s performance. It is of main relevance to identify possible variables in the interviewer-examinee relation when they are interacting. This research aims at analyzing interviewer roles regarding reliability and validity exam. In addition, the main objective is to investigate features involved in interviewer attitudes which can cause an impact on the interaction and on examinee´s performance. Based on results, this study collects some evidences related to validity and reliability of oral proficiency exams focusing interviewer s role, in order to provide some referrals for reflecting on training interviewers and examiners.
Keywords: Proficiência oral; Celpe-Bras; Interação face a face; Papel do entrevistador; Oral assessment; Interviewers role; LINGUISTICA, LETRAS E ARTES::LINGUISTICA